Estimating nitrogen budgets for soil-crop systems - Meisinger, J.J.=700 1 Randall, G.W.
Sumario (En)
Ilus.; 63 ref.
Keywords: PRESUPUESTO; SISTEMAS DE CULTIVO; NITRATOS; NITROGENO; FIJACION DEL NITROGENO; COMPOSICION APROXIMADA; ABONOS NITROGENADOS